Drug induced interstitial lung disease in oncology phase I trials. Issue 12 (December 2016) - Yonemori, Kan; Hirakawa, Akihiro; Kawachi, Asuka; Kinoshita, Fumie; Okuma, Hitomi; Nishikawa, Tadaaki; Tamura, Kenji; Fujiwara, Yasuhiro; Takebe, Naoko
Abstract : Interstitial lung disease is a serious drug‐related condition that can cause life threatening organ failure. The incidence and risk factors of drug‐induced interstitial lung disease (DILD) are unknown in oncology phase I trials. This study analyzed clinical information from 8906 patients with malignancies who were enrolled in 470 phase I trials sponsored by the Cancer Therapy Evaluation Program, National Cancer Institute, from 1988 to 2014. Logistic and Cox statistical analyses were utilized to determine clinical differences between patients who developed DILD and patients who did not. In this study, the overall incidence rate of patients with pulmonary toxicity was 2.7%. The overall incidence rate for DILD was 0.77%, whereas for grade 3 or 4 DILD it was 0.31%. Median time to occurrence of DILD was 1.4 months. The Cox hazard analysis indicated smaller body surface area and a combination of thoracic radiation with investigational drug regimens were significant risk factors for time to occurrence of interstitial lung disease. Investigators should carefully monitor for DILD in oncology patients enrolled in phase I trials with identified risk factors. A 6‐month observation period would be sufficient to detect the onset of most DILD in such patients. Abstract : There is no clinical research using big data including various oncology phase I trials to clear incidence and pattern of DILD in phase I trials and risk factors. The investigator could avoid patient with risk factors for DILD to enroll in phase I trials and could carefully observe patient with risk factor in their phase I trials.